Optimization of an organosolv method using glycerol with iron catalysts for the pretreatment of water hyacinth. (February 2020) - Santana, Joselaine Carvalho; Souza Abud, Ana Karla; Wisniewski, Alberto; Navickiene, Sandro; Romão, Luciane Pimenta Cruz
Abstract: Organosolv pretreatment reactions with glycerol, applied to water hyacinth, were performed with evaluation of the effects of the following variables: time (10–120 min), temperature (100–220 °C), solid/liquid ratio (1–6%), water percentage (0–40%), and cobalt ferrite (CoFe2 O4 ) catalyst percentage (0–10%). The objective was to optimize the process in order to maximize the yield of sugars in subsequent enzymatic hydrolysis. The optimized condition obtained using a 2 5−1 experimental design was as follows: time of 10 min, temperature of 220 °C, solid/liquid ratio of 6%, 0% water, and 0% catalyst, which resulted in 37% release of sugars. Other sources of iron were also tested (FeCl3 and FeSO4 ). Unlike CoFe2 O4, these added iron salts presented activity, under the optimal condition. The use of FeSO4 and FeCl3 at 0.1 mol.L −1 increased the release of sugars to 41 and 51%, respectively. It was evident that the activity of the iron was determined by the form in which it was present. The findings contribute to understanding the action of iron and other metal salts in pretreatment reactions. Graphical abstract: Image 1 Highlights: Optimization of the most important variables by experimental design 2 5−1 . First work on the pre-treatment of water hyacinth with iron-based catalysts. First study that evaluated organosolv pretreatment with glycerol + CoFe2 O4, FeCl3 and FeSO4 . The organosolv pretreatment with glycerol + FeCl3 showed promise. Better understanding of the action of metallic salts in pretreatment reactions.